TARIFF POLICY AND DIGITAL GOVERNANCE IN COAL-SECTOR NON-TAX REVENUE: A SYSTEMATIC LITERATURE REVIEW ON FISCAL OPTIMIZATION - Syafardi, Heri; Wati, Lela Nurlaela; Ispriyahadi, Heri (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Non-Tax Revenue (NTR) from the coal sector constitutes an important component of fiscal resources in resource-dependent economies. However, existing studies tend to examine tariff policy and digitalization as separate instruments, with limited synthesis on how their interaction shapes revenue optimization within extractive governance frameworks. This study aims to address this gap by systematically reviewing the literature on the role of tariff policy and digital governance in optimizing coal-sector NTR. This study employs a non-empirical qualitative SLR. Relevant national and international journal articles, policy reports, and academic publications published within the last decade were identified through structured database searches and screened using predefined inclusion and exclusion criteria. The selected literature was analyzed using narrative and thematic synthesis to identify recurring patterns, governance mechanisms, and conceptual linkages related to NTR optimization. The results indicate that tariff policy remains a central fiscal instrument in coal-sector NTR management, particularly when tariff structures are adaptive, transparent, and aligned with administrative capacity. The literature also shows that digitalization enhances NTR management indirectly by improving administrative efficiency, data accuracy, compliance assurance, and inter-agency coordination. Importantly, the findings suggest that digitalization alone is insufficient to optimize NTR outcomes without coherent institutional frameworks and effective governance coordination. The integrated synthesis reveals that tariff policy and digitalization are mutually reinforcing when implemented in a coordinated manner. Digital governance mechanisms strengthen the credibility and enforceability of tariff policy, while sound tariff design provides the fiscal foundation for effective digital implementation. This interaction constitutes the main conceptual contribution of the study.